Kecerdasan Buatan Dan Transformasi Perkuliahan Studi Islam: Analisis Kritis Penerapan Ai Dalam Metodologi Tafsir Dan Hadits Di Era Digital - Nursita Rahman; Muhammad Qomarullah; Mutiara Salabilla; Fatlam Alqaustar; Muhammad Saepudin; M.Revaldy Exfriza (Sekolah Tinggi Agama Islam (STAI) Bumi Silampari, 2026)
The study of Tafsir and Hadith (STH) is a core discipline in Islamology that serves as an epistemic foundation for understanding revelation. However, the study faces significant challenges in dealing with issues of textual interpretation, interdisciplinary integration, and global professional qualification demands. This study aims to analyze the methodological shift and impact of the integration of artificial intelligence (AI) technology on the STH curriculum in Islamic Universities (PTI). The method used is qualitative-analytical based on literature studies from internationally reputable journals with a focus on curriculum framework analysis, source authority debates, and the adoption of linguistic computing. Key findings point to a crucial shift in the methodology of Hadith study from the acceptance of passive sanad authority to active confirmation, in which the Qur'an is positioned as an epistemic filter to the content of the Hadith. On the other hand, the adoption of Natural Language Processing (NLP) technology is a crucial tool for semantic analysis of sacred texts that has the potential to provide quantitative solutions to the demands of textual coherence. The study also found that the competency profile of STH graduates should be expanded to include the integration of digital skills to meet the demands of the global job market. The implications of this report suggest curriculum reform that marries the depth of classical science with modern research capabilities and increased the capacity of lecturers.